Hubungan Kesepian dan Nomophobia pada Mahasiswa Fakultas Ekonomi Universitas Prima Indonesia Medan - Kenny Kenny; Meilissa Katili; Michelle Leslie; Priscillia Wijaya (Departement of Mathematics Education, 2023)
This study aims to determine the relationship between loneliness and nomophobia in students. The research subjects used in this study were 100 students of the Faculty of Economics, Prima Indonesia University using the method quota sampling. The hypothesis in this study is that there is a positive relationship between loneliness and homophobia in students of the Faculty of Economics, Prima Indonesia University. The results of the analysis using correlation techniquesPearson Product Moment. Where r = 0.705 with a Sig of 0.000 (p <0.05) with an effective contribution of 70.5% nomophobia affects loneliness, meaning that the higher the nomophobia, the higher the loneliness experienced by students. In the hypothetical test, 64% have a moderate nomophobia tendency, 36% have a high nomophobia tendency, 7% have a high nomophobia tendency.lonely while 93% have a high tendency to be lonely. The effective contribution of the nomophobia variable to loneliness is 70.5%, the remaining 29.5% is influenced by other factors such as age, negative views of oneself, low self-esteem. All of these studies use the help of the SPSS version 17.0 for windows.